Practical Philosophy of I. Kant and Problem of Foundation of Law - Šerpytytė, Rita (Problemos, 1990)
The Kantian concept of practice is considered. It is claimed that the normative (practical) disposition reaches the stage of self-consciousness in the philosophy of I. Kant in the sense that the attempts of theoretical combination of the principles of freedom and necessity are abandoned here. The author of the article demonstrates how, based upon the normative disposition, the origin of laws and morals as well as their interrelation are substantiated.